1060 Novel Case of REM Behavior Disorder in a Pediatric PSG. (12th April 2019) - Al-Shawwa, Bahauddin; Pierson, Grant
Abstract: Introduction: Rapid eye movement (REM) behavior disorder (RBD) in the pediatric population is considered a rare disorder. Associated diseases have been published in case reports including neurodegenerative disease, autism, narcolepsy, Smith-Magenis Syndrome and Moebius Syndrome. We report a novel pediatric case of RBD as a result of neurologic injury from a non-demyelinating disease. Report of Case: Four-year-old female was born prematurely at 23 weeks and 6 days. Her neonatal intensive care unit (NICU) stay was complicated with congenital CMV infection and periventricular leukomalacia (PVL). After hospitalization required oxygen for 4 months and weaned successfully. She was later hospitalized at the age of 3 for acute respiratory distress syndrome (ARDS) with viral pneumonia at which time she was found to have bronchomalacia and chronic lung disease. During her clinical follow up her mom described her to be a restless sleeper along with snoring and nocturnal arousals. A full night polysomnogram (PSG) was performed showing REM without atonia. There was no evidence of sleep disorder breathing or seizure activity. After in depth review there was no evidence or history of autism, seizures, narcolepsy, neurodegenerative disease, rare genetic syndromes, or RBD-inducing medications. The etiology of her RBD was determined to be related to her underlying neurologic injury in the form of periventricular leukomalacia. Conclusion: RBD is usually seen in the adult population with infrequent presentations in children. The RBD in this case is novel as it is likely due to her underlying neurologic injury from congenital CMV infection and/or prematurity in the form of periventricular leukomalacia. Awareness of such problem may help to identify patients at increased risk for such disease and providing therapeutic interventions if needed. Support: N/A